India's founding moment : the constitution of a most surprising democracy - Khosla, Madhav (Harvard University Press, 2020)
"How did the founders of the most populous democratic nation in the world meet the problem of establishing a democracy after the departure of foreign rule? The justification for British imperial rule had stressed the impossibility of Indian self-government. At the heart of India's founding moment, in which constitution-making and democratization occurred simultaneously, lay the question of how to implement democracy in an environment regarded as unqualified for its existence. India's founders met this challenge in direct terms-the people, they acknowledged, had to be educated to create democratic citizens. But the path to education lay not in being ruled by a superior class of men but rather in the very creation of a self-sustaining politics. Universal suffrage was instituted amidst poverty, illiteracy, social heterogeneity, and centuries of tradition. Under the guidance of B.R. Ambedkar, Indian lawmakers crafted a constitutional system that could respond to the problem of democratization under the most inhospitable of conditions. On January 26, 1950, the Indian constitution-the longest in the world-came into effect. More than half of the world's constitutions have been written in the past three decades. Unlike the constitutional revolutions of the late-eighteenth century, these contemporary revolutions have occurred in countries that are characterized by low levels of economic growth and education; are divided by race, religion, and ethnicity; and have democratized at once, rather than gradually. The Indian founding is a natural reference point for such constitutional moments-when democracy, constitutionalism, and modernity occur simultaneously"--